Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.18203/2320-1770.ijrcog20180509
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the effect of time interval between hCG and IUI and sperm preparation and IUI

Abstract: INTRODUCTIONIntrauterine Insemination (IUI) along with controlled ovarian stimulation has been a widely used method in management of women with infertility. IUI remains a relatively inexpensive, less invasive and easy to perform procedure, which if timed well can give favorable results. It is used in male factor infertility, minimal to mild endometriosis, PCOS, cervical factor or unexplained infertility. IUI has various determinants of success. Of these, sperm morphology, method of sperm preparation, cause of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Agrawal and colleagues investigated the difference between doing IUI between 36 to 40 hours and more than 40 hours after hCG injection. They assessed 624 cycles and concluded that the pregnancy rate is significantly higher when IUI is done between 36 to 40 hours after hCG injection ( 27 ). The problem of their work is that they have not indicated a precise time.…”
Section: Discussionmentioning
confidence: 99%
“…Agrawal and colleagues investigated the difference between doing IUI between 36 to 40 hours and more than 40 hours after hCG injection. They assessed 624 cycles and concluded that the pregnancy rate is significantly higher when IUI is done between 36 to 40 hours after hCG injection ( 27 ). The problem of their work is that they have not indicated a precise time.…”
Section: Discussionmentioning
confidence: 99%